ChemInform Abstract: Asymmetric [3 + 2] Cycloaddition of Methyleneindolinones with N, N′‐Cyclic Azomethine Imines Catalyzed by a N, N′‐Dioxide—Mg(OTf)2 Complex. Issue 9 (February 2016) - Yin, Chengkai; Lin, Lili; Zhang, Dong; Feng, Juhua; Liu, Xiaohua; Feng, Xiaoming
Abstract: An asymmetric 1, 3‐dipolar cycloaddition of methyleneoxindoles and cyclic azomethine imines affords spirocyclic pyrazolidines in excellent yields and enantioselectivities under mild reaction conditions.